Dynamic load shifting for the abatement of GHG emissions, power demand, energy use, and costs in metropolitan hybrid wastewater treatment systems. (15th July 2021) - Reifsnyder, Samuel; Cecconi, Francesca; Rosso, Diego
Highlights: Dynamic load shifting between hydraulically connected wastewater treatment plants. Case study of a hybrid system comprised by 1 centralized and 7 satellite facilities. Different load shifting schedules to reduce costs, energy and indirect emissions. Up to 25% in power reduction without the need to shutdown treatment operations. Ability to equalize centralized influent flow without building equalization basins. Abstract: The installation of satellite water resource recovery facilities (WRRFs) has strengthened the ability to provide cheap and reliable recycled water to meet the increasing water demand of expanding cities. As a result, recent studies have attempted to address the problem of how to optimally integrate satellite systems with other sectors of the urban sphere, such as the local economy, the power supply, and the regional carbon footprint. However, such studies are merely based on the spatial domain, thus neglecting potential time-dependent strategies that could further improve the sustainability of metropolitan water systems. Therefore, in this study a new conceptual framework is proposed for the dynamic management of hybrid systems comprised of both centralized and satellite WRRFs. Furthermore, a novel set of integrated real-time control (RTC) strategies are considered to analyze three different scenarios: 1) demand response, 2) flow equalization of the centralized WRRF and 3) reduction of greenhouse gas emissions. Data from a case study in California is used to develop an integrated dynamic model of a system of 8 facilities. Our results show that by dynamically shifting the dry-weather influent wastewater flows between hydraulically connected WRRFs, a reduction in power demand (up to 25%), energy use (4%), operating costs (8.5%) and indirect carbon emissions (4.5%) can be achieved. Therefore, this study suggests that a certain degree of hydraulic interconnection coupled with dynamic load-shifting strategies, can broaden the operational flexibility and overall sustainability of hybrid WRRF systems. Graphical abstract: Image, graphical abstract